The analysis of clean water need for fishing activities in Kutaraja Fishing Port, Aceh Indonesia. Issue 1 (2nd January 2021) - Rizwan, Thaib; Kandi, Oni; Jalil, Zulkarnain; Setiawan, Ichsan; Maulana, Riyan; Ranti, Desde Mona Vridia; Zulfahmi, Ilham; Muchlis, Yusrizal; Muhammad, Muhammad; Chaliluddin, Makwiah A.
ABSTRACT: The fishing port provides some services in fishing activities, including clean water supplies. This study aimed to determine the supply mechanism for the clean water needs in fishing activities at Kutaraja Fishing Port. The case study method was used by analysing the level of clean water needed fishermen need. The results showed a theoretical demand of clean water in fishing activities was approximately 7, 497, 871.247 tonnes/year, encompassing the clean variant for fishing at 34, 412.7 tonnes/year, washing catches at 462, 402.19 tonnes/ year and cleaning the fishing equipment at 1, 056.36 tonnes/year. Cumulatively, the clean water requirements for actual fishing activities at the Kutaraja Fishing Port was equivalent to 13, 237.52 tonnes/year. This results from the demand during the washing of catches and also in equipment cleansing.